Sliding scale regimen versus basal bolus insulin regime for hyperglycemia management in hospitalized patients with type 2 diabetes - Jaafar Saadoon, Sarah; Hamid Al-Anbari, Hayder; Thair L. Jabbar; M. Mostafa, Fatma (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Since type-2 diabetes mellitus (T2DM) is becoming more common, it is crucial to implement an appropriate care plan for these patients' hyperglycemia to lower the risk of complications. While Sliding Scale Insulin (SSI) has been the traditional approach, Basal-bolus insulin (BBI) therapy is a promising strategy and is increasingly recommended. We aimed to compare the efficacy of SSI versus BBI regimens in hospitalized patients with T2DM. Methods: The demographics, complications, and type of insulin therapy for type 2 diabetic hospitalized patients were recorded from patients’ archived documents. Results: We observed that 59.7% of the patients were treated for SSI accompanied by macrovascular complications. While 37.8% of patients treated with BBI had macrovascular complications, the difference between the BBI & SSI groups was statistically significant. For microvascular complications, also, a statistically significant difference was detected between the BBI & SSI groups (P-value = 0.001). Only 18.6% & 17.2% of the patients developed hypoglycemia in the BBI group & SSI group, respectively. We evaluated the efficacy of both treatments on daily random blood glucose (RBG) in our patients for 1 week; a slight decrease in RBG was observed between the first & the seventh days of treatment in the SSI group. An obvious improvement was observed in the BBI, indicating that BBI was more effective at controlling RBG than SSI. Conclusion: Our study demonstrated that BBI therapy was superior to SSI therapy in achieving ideal blood glucose levels, with fewer hypoglycemic episodes and cardiovascular events.